THE CHEMICAL LABORATORY WORK CONSIDERING THE SAFETY - FESZTEROVÁ, Melánia (Trends in education, 2009)
The problem of safety and safeguard of health in chemical laboratory is in close connection with theoretical knowledge of the chemistry students and their skills in laboratory exercises. The most chemical substances (elements, compounds) that students work with while making chemical experiments, could endanger the health. Each chemical substance or chemical preparation might represent possible danger for people and environment. The valuation of existing chemical compounds risk consist of collection, exchange and availability of information about existing chemical compounds and their evaluation for life and health of people and environment. The preventive arrangements, basic knowledge of chemical compounds qualities, correct manipulation with them, but also first aid could save the life.The presented contribution is focused on work safety with chemical compounds (elements, compounds) according to occupational health and safety in chemical laboratory. It is inevitable to remember occupational health and safety because of making chemical experiments and for the professional future. The safety rules represent theoretical entrance to laboratory work and will be present with the students all the time while working in chemical laboratory.
Keywords: chemical laboratory; chemical compound; chemical preparation; of safety and safeguard of health.